Implementation of Articles 112 and 127 of Law Number 35 of 2009 concerning Narcotics in Judge’s Verdict Number 183/Pid.Sus/2025 at the Malang District Court, Indonesia - Raihan, Alief (Proceedings of International Conference of Graduate School on Sustainability, 2026)
Law Number 35 of 2009 concerning Narcotics regulates narcotics control through repressive and rehabilitative approaches, with Articles 112 and 127 as the main provisions. This study analyzes the implementation of these two articles through a case study of Judge’s Verdict Number 183/PidSus/2025/PN Malang, in which a defendant was sentenced to 5 years and 6 months in prison for possession of 0.63 grams of crystal methamphetamine, which is categorized as distribution of narcotics. The method used in this study is a normative legal method, along with a statutory approach, to analyze the case in depth using secondary data and referring to the prevailing regulations. In this article, it is found that the implementation of the law on narcotics tends to be repressive, because judges tend to ignore mandatory rehabilitation first, as stipulated in Article 103, thus reducing its effectiveness in reducing the abuse of narcotics. Some factors play a role in this verdict, including limited evidence and the availability of rehabilitation facilities. Thus, it is recommended to implement a more just verdict towards abusers rather than punishing them, since criminal law is also considered as the ultimum remedium contrary to humanitarian principles, and also less effective in dealing with the drug problem.